Novel Electrochemical Flow Injection Procedure for Albendazole Determination using Boron-doped Diamond thin Film Electrode - Watthanachaiyapong Janhom (2019)
© 2019, Pleiades Publishing, Ltd. Abstract: The homemade electrochemical cell for electrochemical determination of albendazole using boron-doped diamond (BDD) thin film electrode is developed. Electrochemical activity of albendazole was investigated by cyclic voltammetry in 0.10 M phosphate buffer containing 20% (v/v) methanol at pH 2.5. Using the BDD electrode well-defined and highly reproducible cyclic voltammogram was obtained with current signal-to-background ratio of higher than those obtained from the glassy carbon electrode. Flow injection analysis system with amperometric detection using the homemade thin-layer electrochemical flow-through cell with BDD electrode was studied. The hydrodynamic voltammogram of the drug exhibited single well defined maximum oxidation peak at 0.95 V versus Ag/AgCl. A low detection limit of 2 ppm was obtained. The current–concentration relationship was rectilinear over the concentration range of 3.3‒150 ppm. The proposed method was applied to albendazole tablets with satisfactory results.